Intermittent parathyroid hormone promotes cementogenesis in a PKA‐ and ERK1/2‐dependent manner. Issue 9 (9th May 2019) - Xu, Yang; Lv, Chunxiao; Zhang, Jiawei; Li, Yuyu; Li, Tiancheng; Zhang, Cheng; Chen, Jianwei; Bai, Ding; Yin, Xing; Zou, Shujuan
Abstract: Background: Intermittent parathyroid hormone (PTH) promotes cementogenesis and provides a promising biotherapeutic to rehabilitate resorbed roots. However, the underlying mechanisms remain inconclusive. Cyclic aenosine monophosphate (AMP)‐dependent protein kinases A (PKA) and extracellular signal‐regulated MAP kinases 1/2 (ERK1/2) are key regulators of bone remodeling. The present study aims to investigate whether PKA and ERK1/2 are involved in the process of intermittent PTH‐promoted cementogenesis. Methods: Sprague‐Dawley rats in experimental group (n = 30) received a daily subcutaneous injection of PTH and the control (n = 30) received placebo vehicle for 1, 2, 3, 4, and 5 weeks. Results were evaluated by hematoxylin and eosin and immunohistochemistry staining. In vitro, OCCM‐30 cells were incubated with intermittent PTH. H89 and U0126 were used to determine the role of PKA and ERK1/2, respectively. The cementogenic results were analyzed by reverse transcription‐polymerase chain reaction (RT‐PCR), western blotting, alkaline phosphatase activity assay and Alizarin Red S staining. The interaction of PKA and p‐ERK1/2 was determined by co‐immunoprecipitation (Co‐IP). Results: Intermittent PTH exerted anabolic effect on cellular cementum in developing teeth with elevated expression of osteocalcin, osteopontin, and PKA (catalytic subunit) in PTH injection group. The promoting effects of intermittent PTH on cementogenesis and osteogenic differentiation were abrogated by H89 and U0126 in vitro, respectively. Blocking of PKA pathway downregulated intermittent PTH‐induced ERK1/2 phosphorylation. Conclusions: Intermittent PTH promotes cementogenesis in a PKA‐ and ERK1/2‐dependent manner. In this process, PKA and p‐ERK1/2 interact with each other. These results support the future biotherapeutic applications of PTH in cementum resorption.